2017
DOI: 10.1080/17543266.2017.1378730
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the fashion consumer in a transparent business model

Abstract: This paper focuses on the relationship between fashion consumers and retailers in the transparency of supply chains and public communication of brand's corporate social responsibility (CSR). Adopting a qualitative, mixedmethods approach, this study explored the current industry situation with regards to the information being disclosed to external stakeholders such as consumers. Following the development of a conceptual framework informed by an in-depth literature search, the study aimed to contribute to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This finding corroborates the ideas of Stål and Jansson [69], who suggested elements of reciprocal responsibility between retailers and consumers are crucial to achieving sustainability. This is also in line with the assertions by James and Montgomery [19], Belz [20], and Yang, Song [21] that retailers have the power to connect consumers and suppliers to incorporate sustainability across the supply chain [21]. However, whilst the roles of consumers and retailers are crucial in managing end of lifecycle garments for sustained competitive advantage, our findings reveal the need for collaboration across all supply chain agents, from upstream to downstream.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding corroborates the ideas of Stål and Jansson [69], who suggested elements of reciprocal responsibility between retailers and consumers are crucial to achieving sustainability. This is also in line with the assertions by James and Montgomery [19], Belz [20], and Yang, Song [21] that retailers have the power to connect consumers and suppliers to incorporate sustainability across the supply chain [21]. However, whilst the roles of consumers and retailers are crucial in managing end of lifecycle garments for sustained competitive advantage, our findings reveal the need for collaboration across all supply chain agents, from upstream to downstream.…”
Section: Discussionsupporting
confidence: 89%
“…Within the context of the current paper, the role of supply chain agents is crucial in moving towards sustainability. James and Montgomery [19], Belz [20], and Yang, Song [21] argued that retailers have a significant role to play through their power and control, and capacity to connect consumers and suppliers, acting as "ecological gatekeepers" [21]. However, Taghikhah, Voinov [22], Shen [23], Thorisdottir and Johannsdottir [24], and Cervellon and Wernerfelt [25] all suggested that sustainability activities should not stop with retailers but should also extend to cover the post-consumption period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of clarity concerning the term "supply chain transparency" and the absence of a consistent definition have also been pointed out by various other authors (e.g., Egels-Zandén et al 2015;James and Montgomery 2017). Other terms and concepts are intermingled with supply chain transparency (Sodhi and Tang 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Promoting SF on social media has been found to increase purchase intention, positive attitudes and self-efficacy (de Lenne and Vandenbosch, 2017). Across all of these channels, brands are encouraged to be transparent and “open” with customers (Beard, 2008; Henninger et al , 2015; James and Montgomery, 2017c) although the opaque nature of SF as a concept makes the scope of overclaiming a major area of concern.…”
Section: Sustainable Fashion: a Pragmatic View On Production And Consumptionmentioning
confidence: 99%